Communication of heritage through interpretive itineraries and their contribution to the development of the creative economy - Saavedra-Ordinola, Deyvi (Mercurio Peruano, 2016)
Considering the growing progress in the protection and conservation of Peru's cultural heritage, this article aims to provide an approach to the limitations on its scope of communication, primarily through a specific product: the interpretive cultural itineraries. After a brief review of the status of these goods in Piura region as territorial delimitation and under the description of a case of cultural routes, some edges are provided on how heritage is in all areas of management but even more in the promotion and communication, a key part of a new economic paradigm framework: the creative economy.